Serial Diffusion Tensor Imaging of the Optic Radiations after Acute Optic Neuritis - Scott C. Kolbe; Anneke van der Walt; Helmut Butzkueven; Alexander Klistorner; Gary F. Egan; Trevor J. Kilpatrick (Journal of Ophthalmology)
Previous studies have reported diffusion tensor imaging (DTI) changes within the optic radiations of patients after optic neuritis (ON). We aimed to study optic radiation DTI changes over 12 months following acute ON and to study correlations between DTI parameters and damage to the optic nerve and primary visual cortex (V1). We measured DTI parameters [fractional anisotropy (FA), axial diffusivity (AD), radial diffusivity (RD), and mean diffusivity (MD)] from the optic radiations of 38 acute ON patients at presentation and 6 and 12 months after acute ON. In addition, we measured retinal nerve fibre layer thickness, visual evoked potential amplitude, optic radiation lesion load, and V1 thickness. At baseline, FA was reduced and RD and MD were increased compared to control. Over 12 months, FA reduced in patients at an average rate of −2.6% per annum (control = −0.51%; p=0.006). Change in FA, RD, and MD correlated with V1 thinning over 12 months (FA: R=0.450, p=0.006; RD: R=-0.428, p=0.009; MD: R=-0.365, p=0.029). In patients with no optic radiation lesions, AD significantly correlated with RNFL thinning at 12 months (R=0.489, p=0.039). In conclusion, DTI can detect optic radiation changes over 12 months following acute ON that correlate with optic nerve and V1 damage.